Efek Pemberian EDTA dan Macam Bahan Organik Terhadap Penyerapan Logam Berat Pb (Timbal) Pada Tanaman Hanjuang (Cordyline fruicosa L.) - ike melinda putri; Anis Rosyidah; Nurhidayati Nurhidayati (AGRONISMA, 2019)
This study aimed to determine the effect of EDTA and various types of organic matter on the content of extracted heavy metals Pb in soil, roots and shoot of Cordylinefruicosa L., and growth of CordylinefruicosaL. This research is a pot experiment conducted at the greenhouse and laboratory of the Agriculture Faculty, University of IslamMalang, which started in August to November 2018. This experiment used a factorial randomized block design (RBD) consisted of two factors. The first factor was EDTA application whichÂ consisted of two levels, namely: E0: Without EDTA, E1: Added EDTA and the second factor was Â the type of organic material which consisted of three levels, namely: M0: Without organic matter, M1: Chicken manure, and M2: Thitoniadiversofolia L Each treatment was repeated 3 times with 3 plant samples. Thus, there were 54 pots of hanjuang plant. The results showed that application of EDTA and organic matter gave more residual Pb heavy metals than control, where the highest Pb heavy metal content was found in the treatment of E1M2 (EDTA + Tithoniadiversifolia L.). This is caused by the phytostabilization process. The E1M2 treatment (EDTA + chicken manure) tends to have the highest Pb concentration in roots and shoot of 0.393 ppm and 0.215 ppm. Increasing the concentration of Pb in the shoot had a negative effect on the growth of Cordylinefruicosa L.Â plants.